Interfacial modulation of ZnIn2S4 with high active Zr-S4 sites for boosting photocatalytic activation of oxygen and degradation of emerging contaminant - Hui Li; Ji, Haodong; Jiajia Liu; Liu, Wen; Li, Fan; Zhurui Shen (Applied Catalysis B: Environmental, 2023)
Interfacial modulation of catalysts for constructing active sites can greatly promote its catalytic activity, while the mechanism on reactive species production at different interfaces still needs to be revealed. In this study, Zr-S4 active sites were usefully constructed on ZnIn2S4 nanosheets, which effectively modulated the reaction interface and band structure, thus boosting the photocatalytic activity. The optimized material (Zr1.2-ZIS) showed a ∼3-fold kinetic rate constant for photocatalytic degradation of tetracycline compared with the pristine ZnIn2S4. Moreover, TC underwent a different degradation pathway over the modified catalyst due to regulation of reactive species after photo-activation. The Zr-S4 centers were energetically favorable for activating O2 into •O2- and •OH, as a more reactive d-band electron was obtained and the adsorption of •O2- as well as its further conversion into •OH was promoted. Theoretical calculations on Fukui index and toxicity also confirmed the dramatical toxicity reduction during TC degradation by Zr1.2-ZIS.
Keywords: Emerging contaminant; Interfacial modulation; O activation; Photocatalysis; ZrS active sites